Association of acute pyelonephritis with double-J ureteral stenting: a nationwide population-based case control study. (2nd January 2021) - Chen, Szu-Ju; Huang, Chi-Ping; Chiu, Kun-Yuan; Chen, Huey-Yi; , Lu-Ting; Chiu,; Chen, Yung-Hsiang; Chen, Wen-Chi
Abstract: Objective: Urinary Tract Infections (UTIs) due to ureteral catheters has been frequently seen. The risk factors of this include both timing and those of the female gender. However, the association of Acute Pyelonephritis (APN) with use of ureteral DJ stents has rarely been investigated. Materials and Methods: This study enrolled a total of 6, 459 patients who were being treated with a ureteral catheter over a 10 year period from the nationwide database of Taiwan's National Health Insurance Bureau. From these subjects, episodes of APN were found in a total of 500 patients. Additionally, 2, 000 patients without APN were randomly enrolled as a control group in order to analyze the associated factors. Results: The results indicate that the percentage of those with regards gender, age, duration of implantation, ureteral stent type, hypertension, T2DM, presence of urinary tract infection, benign prostate hyperplasia and pregnancy status were significantly statistically higher in APN patients than non-APN patients. APN did not associate with the use of antibiotics, urolithiasis, chronic kidney disease, malignancy, or uric acid stone in patients with a ureteral catheter. Conclusion: In conclusion, patients with a ureteral catheter associated with APN should be given close attention with regards to the above risk factors. Early removal of the catheter is the best policy for the prevention of APN.